Knowledge and attitudes towards concussion in UK-based male ice hockey players: A need for attitude change?. Issue 2 (April 2019) - Hutchinson, Sarah; Ellison, Paul; Levy, Andrew; Marchant, David
Objective: Concussion is a common injury in ice hockey, and previous research suggests some misconceptions and unsafe attitudes amongst players. The purpose of this study was to assess sport concussion knowledge, attitudes and the effect of sport concussion history in UK-based male ice hockey players across three levels of competition: professional, semi-professional and amateur. Methods: Sixty-one participants across a number of UK ice hockey teams completed the Rosenbaum Concussion Knowledge and Attitudes Survey and reviewed a series of statements to assess knowledge (concussion knowledge index), attitudes (concussion attitude index) and misconceptions of concussion. Results: Level of competition and concussion history had no significant effect on concussion knowledge index or concussion attitude index. A positive significant relationship exists between playing experience and concussion knowledge index and concussion attitude index. Statements identified common misconceptions and areas of accurate knowledge regarding concussion symptoms suggesting that male ice hockey players have a higher level knowledge compared to a sample of the UK general public. Playing experience was associated with increased knowledge and increasingly safe attitudes towards concussion. Conclusion: Despite knowledge relating to loss of consciousness and correct management of symptoms being generally accurate, there are worryingly unsafe attitudes regarding aspects of concussion. Such attitudes may well pose significant threats to players' safety and long-term health.